Sector of Spatial Organization of Society of Institute of Geography: History of Development and Scientific Achievements - Pidgrushnyi, G. P.; Nahirna, V. P. (Ukrainian Geographical Journal, 2024)
The article highlights the scientific activity in the sector of spatial organization of society over the sixty-year period from the hour of its foundation in 1964 and until now. There are three main stages in the development of the sector: from the time of foundation until 1991, when the Institute of Geography was created; from the 90s of the 20th century. Until the end of the first decade of the XXI century; current stage. For each of the stages, the main research topics, scientific developments are characterized, and the leading scientific publications are presented. Particular attention is paid to the connection of scientific topics to the sector with socio-economic processes and the geopolitical situation in Ukraine and the world in recent historical periods. The topics of international scientific projects in which sector scientists participated were discussed. Showing the peculiarity of scientific research to the sector in the minds of wartime.